A moral economy of water: Charity wells in Egypt's Nile delta - ElDidi, Hagar; Corbera, Esteve (Wiley, 2017)
Though commonly viewed as a human right, access to water is often difficult and highly unequal within and between communities, depending on various social and power relations, access mechanisms and property rights regimes. However, moral norms and subsistence ethics can also play a balancing role, enhancing access to water for vulnerable groups and individuals, particularly in contexts of water scarcity. Using the example of a Nile Delta village, this article explores the role of charitable water wells (sobol) in influencing both irrigation and drinking water access relations, by understanding their different modes of governance and the motivations behind their emergence. The article argues that charitable norms underlying sobol are dynamic. They stem from certain moral ideologies concerning religion, property and reciprocity, and while they do greatly enhance access to water, it is with varying degrees, limitations and remaining access discrepancies. Sobol alter property rights relations, extending entitlements to water, but their effectiveness is also limited by existing property rights regimes. Sobol are also limited by existing anti‐cooperative actions, and being embedded in an inequitable access system, they may not fully counterbalance inequitable water access. The limitations of cooperative water access arrangements should be counterweighed and complemented by overarching and equitable water distribution systems.